De otte selesamlere fra ryttergraven i Fregerslev - Bagge, Merethe Schifter (Arkæologi i Slesvig-Archäologie in Schleswig, 2020)
In the spring of 2017, an impressive equestrian chamber grave dating to the late Viking Age was excavated in Fregerslev near Skanderborg, Jutland. Equestrian graves of this quality belong to a very rare category of finds from Viking Age Denmark. The few known finds appear to form a northern and southern geographical group; the southern group is well-represented in the area of Schleswig. The most recent comparable grave was examined in 1983 (Grimstrup, Esbjerg). The chamber grave contained more than 700 gilded and silvered fittings belonging to the harness and bridle of the rider’s horse. Previously, similar finds have been seen only among the finds from e.g. Thumby Bienebek and Grimstrup. The potential of the recent finds from Fregerslev for research into horse harness fittings of the Viking Age elite milieu is therefore immeasurable. The decoration of the bridle consists of different gilded copper alloy strap mounts, e. g. cross-shaped fittings and rectilinear figure-of-eight fittings which have direct parallels to grave finds in Langballigau, Quern-Scheersberg, and Thumby Bienebek located in the area of Schleswig. In addition, metal detectorists have found similar cross-shaped strap mounts scattered around Denmark. This article presents the preliminary results of the excavation and shows the distribution of three different strap mounts. In addition, the question is addressed whether the horse harness can be seen as a symbol of men with a special military rank. There might be a geographical difference in the perception of the harness.